Policy Strategy for Enhancing the Utilization of Research Infrastructure at the National Research and Innovation Agency (BRIN) - Suardi Kadang (POKJANAS PERENCANA KEMENTERIAN AGAMA RI, 2026)
This study is motivated by the suboptimal utilization of research infrastructure at the National Research and Innovation Agency (BRIN), as indicated by the low level of external usage and the imbalance of non-tax revenue (PNBP) between internal and external users. This condition reflects a gap between the significant potential of national research infrastructure and its actual utilization, caused by weak access regulations, unstandardized governance, and fragmented administrative and monitoring systems. The study aims to identify root causes and formulate appropriate policy alternatives. A qualitative policy study approach was employed, using document analysis, problem identification through the USG (Urgency, Seriousness, Growth) method, and evaluation of policy alternatives based on William N. Dunn’s criteria. The findings reveal that the main issue lies in the absence of open access policies and weak service governance. Among the three policy alternatives, issuing a BRIN Head Regulation on Open Access Utilization Policy is identified as the most optimal solution, as it comprehensively addresses the root problems. The study concludes that strengthening open-access regulations, supported by integrated governance and data-driven systems, is key to improving infrastructure utilization. Therefore, it is recommended to establish an open access regulation accompanied by improved service systems, external capacity allocation, and data-based monitoring to enhance collaboration, facility utilization, and contributions to the national innovation system.